Respuestas
Respuesta dada por:
6
Puedes utilizar la fórmula general para resolverlo:
![ax^2+bx+c=0 \\ \\ x= \frac{-b\pm \sqrt{b^2-4ac} }{2a} \\ \\ x^2-4mx-5m^2=0 \\ a=1 \\ b=-4m \\ c=-5m^2 \\ \\ x= \frac{-(-4m)\pm \sqrt{(-4m)^2-4(1)(-5m^2)} }{2(1)}=\frac{4m\pm \sqrt{16m^2+20m^2} }{2} \\ =\frac{4m\pm \sqrt{36m^2} }{2}= \frac{4m\pm6m}{2}=2m\pm 3m \\ x_1=2m+3m=5m \\ x_2=2m-3m=-m \\ \\ \boxed{x=\{5m,-m\}} ax^2+bx+c=0 \\ \\ x= \frac{-b\pm \sqrt{b^2-4ac} }{2a} \\ \\ x^2-4mx-5m^2=0 \\ a=1 \\ b=-4m \\ c=-5m^2 \\ \\ x= \frac{-(-4m)\pm \sqrt{(-4m)^2-4(1)(-5m^2)} }{2(1)}=\frac{4m\pm \sqrt{16m^2+20m^2} }{2} \\ =\frac{4m\pm \sqrt{36m^2} }{2}= \frac{4m\pm6m}{2}=2m\pm 3m \\ x_1=2m+3m=5m \\ x_2=2m-3m=-m \\ \\ \boxed{x=\{5m,-m\}}](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0+%5C%5C++%5C%5C+x%3D+%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D+%7D%7B2a%7D++%5C%5C++%5C%5C+x%5E2-4mx-5m%5E2%3D0+%5C%5C+a%3D1+%5C%5C+b%3D-4m+%5C%5C+c%3D-5m%5E2+%5C%5C++%5C%5C+x%3D+%5Cfrac%7B-%28-4m%29%5Cpm+%5Csqrt%7B%28-4m%29%5E2-4%281%29%28-5m%5E2%29%7D+%7D%7B2%281%29%7D%3D%5Cfrac%7B4m%5Cpm+%5Csqrt%7B16m%5E2%2B20m%5E2%7D+%7D%7B2%7D+%5C%5C+%3D%5Cfrac%7B4m%5Cpm+%5Csqrt%7B36m%5E2%7D+%7D%7B2%7D%3D+%5Cfrac%7B4m%5Cpm6m%7D%7B2%7D%3D2m%5Cpm+3m+%5C%5C+x_1%3D2m%2B3m%3D5m+%5C%5C+x_2%3D2m-3m%3D-m+%5C%5C+++%5C%5C+%5Cboxed%7Bx%3D%5C%7B5m%2C-m%5C%7D%7D)
Saludos!
Saludos!
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años